ANALYSIS OF URINARY TRACT INFECTIONS IN GERIATRIC PATIENTS - Kayali, Suemeyra; Sagmak Tartar, Ayse; Ari, Nuray; Asan, Mehmet Ali; Erdem, Beyza; Akbulut, Hatice Handan (Turkish Geriatrics Soc, 2025)
Introduction: There are some differences in the clinical approach to urinary tract infections in geriatric patients. The aim of this study was to investigate the clinical characteristics of symptomatic urinary tract infections in geriatric patients in a tertiary care hospital and to determine the infectious agents and antibiotic susceptibilities. Materials and Method: The study included geriatric patients (aged over 65) who were followed up for symptomatic urinary tract infection at F & imath;rat University Medical Faculty Hospital between March and September 2023. Results: The study included 258 patients, of whom 164 (63.6%) were male. Clinical analysis of the patients showed that 85.7% of the patients had complicated urinarytract infections, 51.2% had lower urinarytract infections and 61.6% had community-acquired urinary tract infections. A total of 274 isolates were identified, including two uropathogens in 16 patients. Of these, 70.8% belonged to Enterobacterales species and E. coli (42.7%) was the most common isolate. Extended-spectrum beta-lactamase production in Enterobacterales species was 50% in community-acquired strains and 68.9% in hospital-acquired strains. The ampicillin susceptibility of Enterococcus species was 72.7% for community-acquired isolates and 54.5% for hospital-acquired isolates. 68.8% of community-acquired Staphylococcus spp. and 68.8% of hospital-acquired Staphylococcus spp. isolates were methicillin-resistant. Conclusion: In our study, the high prevalence of male patients with complicated urinary tract infections was notable. Furthermore, the antibiotic resistance profiles identified emphasise the need to update treatment strategies and maintain surveillance of resistance in geriatric patients. These findings highlight the importance of a multidisciplinary approach to managing UTIs in geriatric patients, with close collaboration between clinicians and microbiologists.
Keywords: Tertiary Care Centers; Community-Acquired Infections; Anti-Bacterial Agents; Methicillin Resistance; Escherichia coli; Enterococcus